Cost Leadership in Marketing - Nabil Ali Alshboul, Feras; Rashid, Umi Kartini; Harun, Amran; Albert Gisip, Imelda (Penerbit UTHM, 2020)
In the marketing world, there are several kinds of strategies. One of the most important strategy is the cost leadership strategy, this strategy described pursues competitive advantage of the company based on lower price or differentiation or aim. That strategy works by increasing the efficiency of the production and at the same time decreasing the production cost. (Hilman & Kaliappen, 2014).